LE MANAGEMENT DE PROJETS DANS L’ENSEIGNEMENT SUPÉRIEUR MAROCAIN : UNE APPROCHE EXPLICATIVE SELON L’ÉCHELLE DE GRANT ET PENNYPACKER - ABDERMA , AMINE; MAIMOUN, Ahmed (Revue du contrôle, de la comptabilité et de l’audit, 2020)
THIS ARTICLE IS AIMED TO DRAW THE CURRENT STATE OF THE MATURITY LEVEL OF PROCESSES RELATED TO PROJECT MANAGEMENT IN MOROCCAN HIGHER EDUCATION. THIS ANALYSIS CONCERNED THE DIFFERENT FACETS AND STANDARDIZED DIMENSIONS.